Efficacy of Bath PUVA in the treatment of Palmoplantar hyperkeratosis (Mugda Medical College Journal, 2023)
Background: Palmoplantar hyperkeratosis, or palmoplantar keratoderma, is a combination of skin conditions that are characterized by excessive thickening of the skin, mainly on the soles and palms. There are various treatment methods for keratoderma, and one of those methods are treatment through bathwater PUVA. It is a type of photochemotherapy.Objective of the study: The aim of the study was to observe the efficacy of bath PUVA treatment for palmoplantar hyperkeratosis.Methodology: This randomized clinical trial study was conducted at the Department of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. The study duration was 6 months, from September 2007 to February 2008. A total of 30 patients presented with  with palmoplantar hyperkeratosis were enrolled in this study through  random sampling method following the inclusion and exclusion criteria.Results: Majority of participant (33.3%) were from the age group of 31-40 years. The mean ±SD age was 38.40±10.89 years, and the age range of the participants was 20-58 years. 70% of the participants were male, 83.3% were from low socioeconomic class, and 36.7% were businessmen respectively. Histopathological diagnosis revealed that 52% patients had psoriasis, 33% had nonspecific dermatitis, and 10% patients had chronic inflammatory dermatitis. Gradual improvement was observed from baseline to 8 weeks follow-up in regards to palmoplantar surface area involvement, erythema, and hyperkeratosis. 46.7% of the participants reported skin tenderness, and 93.3% have a burning sensation and no other side effects.Conclusion:  Bath PUVA may be an effective option in the treatment palmoplantar keratosis particularly of psoriatic patients. A mild form of nonspecific dermatitis may be treated with bath PUVA.Mugda Med Coll J. 2022; 5(2): 76-81